Relations of eastern Christians with Holy see – the Lyon Council of 1274 and Georgia - Мурман Папашвили; Теа Карчава; Теа Цитланадзе; Бека Квачадзе (Журнал Белорусского государственного университета: История, 2019)
The article presents the issues of close relationship of Georgian Orthodox Church and Royalty with the Roman Curia and Papacy and the attempts of Georgian kings to maintain relations with Europe through Catholic missions in the period of Mongol and Khwarezm invasions are considered in the paper. Also, it is highlighted that, unlike Byzantium, Georgia operat-ing with political motivations had quite different attitude to the solution of the Lyon Council about Union.